2015
DOI: 10.1111/anu.12302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with β-glucan and synbiotics on growth, haemolymph chemistry, and intestinal microbiota and morphology in the Pacific white shrimp

Abstract: The goal of this study was to investigate the effects of dietary supplementation with b-glucan and microencapsulated probiotics (Bacillus subtilis or Pediococcus acidilactici) on growth performance, body composition, haemolymph constituents, and intestinal morphology and microbiota of the Pacific white shrimp Litopenaeus vannamei. Four treatment diets [basal diet (C), b-glucan-containing diet (b-glu), b-glucan plus B. subtilis-containing diet (b-glu+Bs), and b-glucan plus P. acidilactici-containing diet (b-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 43 publications
1
41
1
Order By: Relevance
“…Synbiotics have been previously shown to be beneficial when included in the diet of several fish species such as Rainbow trout, Oncorhynchus mykiss (Rodriguez‐Estrada, Satoh, Haga, Fushimi, & Sweetman, ), Common carp, Cyprinus carpio (Yar‐Ahmadi, Moradi, & Ghysvandi, ), Angelfish, Pterophyllum scalare (Azimirad, Meshkini, Ahmadifard, & Hoseinifar, ), White shrimp, Litopenaeus vannamei (Boonanuntanasarn, Wongsasak, Pitaksong, & Chaijamrus, ) and European lobster, Homarus gammarus L . (Daniels et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Synbiotics have been previously shown to be beneficial when included in the diet of several fish species such as Rainbow trout, Oncorhynchus mykiss (Rodriguez‐Estrada, Satoh, Haga, Fushimi, & Sweetman, ), Common carp, Cyprinus carpio (Yar‐Ahmadi, Moradi, & Ghysvandi, ), Angelfish, Pterophyllum scalare (Azimirad, Meshkini, Ahmadifard, & Hoseinifar, ), White shrimp, Litopenaeus vannamei (Boonanuntanasarn, Wongsasak, Pitaksong, & Chaijamrus, ) and European lobster, Homarus gammarus L . (Daniels et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Within 5 days, the bacterial community in the intestinal tract of shrimp receiving probiotics was shown to be more uniform with the probiotic compared with that of the control group, and the survival rate in shrimp fed probiotic was significantly increased upon challenged with V. parahaemolyticus (Luis‐Villaseñor et al., ). Probiotic supplement has been shown to affect the concentration of lactic acid bacteria, decrease the number of Vibrio spp., and increase the height of intestinal villi in P. monodon (Boonanuntanasarn, Wongsasak, Pitaksong & Chaijamrus, ). The difference in bacterial communities in different segments could have an impact on the functioning of probiotic bacteria and consequently affected the health of the host animal.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in creatinine level may be related to phenolic component such as catechin (Halima et al, ). Meanwhile, Boonanuntanasarn et al () demonstrated that the shrimp fed dietary β‐glucan plus probiotic did not affect statistically the urea concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific community investigated friendly environmental feed additive to substitute the administration of antibiotics and chemical disinfectants. During the last decades, the application of supplemental diets such as probiotics (Abdollahi‐Arpanahi et al, ; Wang & He, ), herbal additive (Duan, Wang, Zhang, Sun, & Wang, ; Pirian, Piri, Sohrabipour, Jahromi, & Blomster, ) prebiotics (Boonanuntanasarn, Wongsasak, Pitaksong, & Chaijamrus, ; Zhao et al, ) and immune‐stimulants (Rattanavichai, Chen, Chang, & Cheng, ; Subramanian, Jang, Kim, Kang, & Heo, ) has been developed in order to improve immunological and biochemical parameters of shrimp. Recently, organic acids (short‐chain fatty acids) and their salts are dramatically reported as supplemental diets for improving resistance to pathogens (Koh, Romano, Zahrah, & Ng, ; Mine & Boopathy, ; Ng, Koh, Teoh, & Romano, ), growth performance (da Silva, Vieira, Mouriño, Bolivar, & Seiffert, ; Sukor et al, ), digestive enzyme activity (Castillo, Rosales, Pohlenz, & Gatlin, ; Duan et al, ; Silva et al, ) and nutrient utilization (Khajepour & Hosseini, ; Romano, Koh, & Ng, ) in various aquatic animals.…”
Section: Introductionmentioning
confidence: 99%